Методологічні проблеми територіального дослідження фольклору: репертуар гуслярів - Джорджевич, С. (Народна творчість та етнологія, 2012)
Contemporary research of the «living» oral epic poetry, with emphasis being placed on understanding textualization as a dynamic process, has brought the change of orientation from formulaic concept to mental text and epic idiolect concept. This also marks a shift in the research which aims towards seeing carriers of tradition as active subjects to adopt the tradition, transfer it to others, to create and present it in a concrete communication situation. Subjective stance towards tradition is introduced as a new relevant research problem. The gusl performing is examined as a part of a personal, family, local, and regional cultural identity, the positioning of tradition and the individual within it through explication and valorization of its elements – repertoire, attitude towards the instrument, and its cultural ethos.